The Deportation of the Polish and Baltic Population to the USSR in 1939–1941: its Regional Specifics - Lebedeva, Natalija (Genocidas ir rezistencija, 2001)
The planning and implementation of deportations from the west of Ukraine and Belorussia, Lithuania, Latvia, and Estonia incorporated into the USSR by force had much in common. All the deportations were prepared and carried out on the basis of decisions carefully worked out by the Soviet Politbiuro, and were an important element of the sovietization policy on these territories. The deportations were part of measures aimed to destroy state, judicial, social, economic, national, cultural, and moral fundamentals, and violently spread the Soviet order on the annexed territories. Methods of their organization and implementation were absolutely identical. All of deportations were the crime against humanity. At the same time there were certain differences. No military operation was carried out and the planned capture of armies did not happen at the time of the Soviet invasion of Baltic states. Accordingly there was no need to transport tens of thousands of POWs to Russia’s remote regions as it was done with remnants of the Polish Army. Also, there were no such mass shootings of officers, policemen, and jail inmates as in the Polish Case. The scale of deportations and numbers of exiled were not as high as on the territories of eastern Po- land. This could be explained by the fact that in the course of depolonization of captured lands, the Soviet Government counted upon collaborative or, at least, passive attitude on the part of the Ukrainian and Belorussian population whose status was far from equal in former Poland. The peoples of Baltic states, which enjoyed national sovereignty before their incorporation into the USSR, considered sovietization as a national humiliation to a larger extent than the peoples who suffered under the Polish or Rumanian yoke. It forced the Stalinist ruling elite of the USSR at first to demonstrate a certain respect towards their local customs and traditions, carry out nationalization of industry and banking slowly and more cautiously (introduction of Soviet currency and unified prices was postponed several times), to refrain from collectivization and mass deportations up till the very eve of the war between the Soviet Union and Germany.